Influence Therapy Murottal on Anxiety Levels in Pre Operation Patients Cataract: A Literature Review - Yunita Aisah Putri; Siti Nuryani; Feni Rosa Junita; Siti Yulianti; Sri Kurnia Dewi (STIKES Hesti Wira Sriwijaya, 2025)
Introduction: High levels of anxiety in pre-operative patient cataract can influence stability physiological and psychological, so that potential bother the way procedure operative. One of the effective non-pharmacological methods in reduce anxiety is therapy murottal, which is believed give effect relaxation through mechanism neurophysiological patient. The purpose of this study was to know the influence therapy murottal to level anxiety in preoperative patients​ cataract. Method: Research This is study secondary use method literature review. Results: Results of literature review of the 5 journals that have been has been shown, shows that therapy murottal effective in lower-level anxiety pre-operative patient cataracts. Effects This supported by findings improvement relaxation, decrease beat heart, and decline level hormone stress like cortisol. Conclusion: Therapy murottal Al-Quran has significant influence in lower-level anxiety pre-operative patients, especially in cataracts patient.